Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran di Indonesia - Husnud Diniyah; Ladi Wajuba Perdini Fisabilillah (Jurnal Ekonomika : INDEPENDEN, 2022)
This research aims to determine the factors that influence the unemployment rate in Indonesia. Several factors analyzed in this research are Human Development Index (HDI), Economic Growth, and minimum wage. This research is a type of quantitative research where the data used is secondary data during 2018 – 2021 and processed using the panel data regression analysis method. The results of this study shows that simultaneously HDI, economic growth, and minimum wages have an effect on the unemployment rate. then partially, HDI has no significant positive effect, while economic growth has a significant negative effect and the minimum wage has an effect significant positive effect on the unemployment rate in Indonesia.